Market imperfections, wealth inequality, and the distribution of trade gains - Reto Foellmi; Manuel Oechslin (University of Bern, Department of Economics, 2010)
Globalization increasingly involves less-developed countries (LDCs), i.e., economies which usually suffer from severe imperfections in their financial systems. Taking these imperfections seriously, we analyze how credit frictions affect the distributive impact of trade liberalizations. We find that free trade significantly widens income differences among firm owners in LDCs: While wealthy entrepreneurs are better off, relatively poor business people lose. Intuitively, with integrated markets, profit margins shrink - which makes access to credit particularly difficult for the least affluent agents. Richer entrepreneurs, by contrast, win because they can take advantage of new export opportunities. Our findings resonate well with a number of empirical regularities, in particular with the observation that some liberalizing LDCs have observed a surge in top-income shares.
Keywords: O11; F13; O16; 330; wealth inequality; trade liberalization; credit market frictions; top incomes; Finanzmarkt; Unvollkommener Markt; Kapital; Einkommensverteilung; Internationale Wirtschaft; Optimale Verteilung; Wirtschaftswachstum; Theorie